PENGARUH MANAJEMEN KINERJA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PENGGUNA JASA TRANSPORTASI - Oktiani, Nurvi; Lestari, Nurlaela Eva Puji; Agustina, Teni (2021)
Transportation system in Indonesia as a general and especially in Jakarta have been integrated and managed for fulfill and increasing demand for user in Public Transportation, the managing of Public Transportation is needed not only demand user but also make connection for user duties, so that can reach efficiency and efficient and achieve satisfaction, one of ways for managing Public transportation with increasing performance management and service quality. The research have a purpose for knowing what extent the impact of Performance management and Service Quality toward increasing of Customer Satisfaction the user of Public Transportation. The Methods of research use Quantitative with ordinal scale, and the amount of samples consist of 400 user of public Transportation in Transjakarta. The Data is taken by Spread of Questionnaire, The Processing data have been used by Statistical Package For Social Sciences(SPSS) with Reliabilities, Validities, Normality of Residual, Multicollinearity, heteroscedasticity, autocorrelation, partial correlation between independent variable and evaluation of Regression. From the result can explain between Performance Management and Service Quality have significant relation toward customer satisfaction beside that it have been significant impact between variables, with determinant coefficient performance management and service quality can explain customer satisfaction with amount 54.5% leftovers can be described with another factors such as customer relationship management and Customer expectation, etc, and the advice in the future for consideration, it is need new strategies or program for increasing customer satisfaction.